Anti-Inflammatory and Immunomodulatory Effects of Probiotics in Gut Inflammation: A Door to the Body - Cristofori, Fernanda; Dargenio, Vanessa Nadia; Dargenio, Costantino; Miniello, Vito Leonardo; Barone, Michele; Francavilla, Ruggiero (Frontiers in Immunology, 2021)
Hosting millions of microorganisms, the digestive tract is the primary and most important part of bacterial colonization. On one side, in cases of opportunistic invasion, the abundant bacterial population inside intestinal tissues may face potential health problems such as inflammation and infections. Therefore, the immune system has evolved to sustain host-microbiota symbiotic relationship. On the other hand, in order to maintain host immune homeostasis, the intestinal microflora often exerts an immunoregulatory function that cannot be ignored. In fact, a field of great interest is the association of either microbiota or probiotics with the immune system with respect to clinical uses. This microbial community regulates some of the host's metabolic and physiological functions, and drives early-life immune system maturation, contributing to their homeostasis throughout life. Changes in gut microbiota can occur through modification in function, composition (dysbiosis), or microbiota-host interplays. Studies on animals and humans show that probiotics can have a pivotal effect in the modulation of immune and inflammatory mechanisms; however, the precise mechanisms have not yet been well defined. Diet, age, BMI (body mass index), medications, and stress may confound the benefits of probiotics intake. In addition to host gut functions (permeability and physiology) all these agents have profound implications for the gut microbiome composition. The use of probiotics could improve the gut microbial population, increase mucus-secretion and prevent the destruction of tight junction proteins by decreasing the number of lipopolysaccharides (LPS). When LPS binds endothelial cells to toll-like receptors (TLR 2, 4), dendritic cells and macrophage cells are activated, and inflammatory markers are increased. Furthermore, a decrease in gut dysbiosis and intestinal leakage after probiotic therapy may minimize the development of inflammatory biomarkers and blunt unnecessary activation of the immune system. In turn, probiotics improve the differentiation of T-cells against Th2 and development of Th2 cytokines such as IL-4 and IL-10. The present narrative review explores the interactions between gut microflora/probiotics and the immune system starting from the general perspective of a biological plausibility to get to the in-vitro and in-vivo demonstrations of a probiotic-based approach up to the possible uses for novel therapeutic strategies.